Spatial and Temporal Variability of Bed Exchange Characteristics of Fine Sediments From the Weser Estuary - Patzke, J.; Nehlsen, E.; Fröhle, P.; Hesse, R. F. (Frontiers in Earth Science, 2022)
Sedimentation of fine grained sediments in estuaries is a natural physical phenomenon influenced by bio-geochemical processes. In the estuarine turbidity maximum (ETM) an enhanced net deposition of these sediments is typically observed due to several processes (e.g. estuarine circulation). Maintenance dredging is a common method to maintain the navigational channel which requires large financial effort and has potential negative impacts on the environment as well. The research at IWB addresses the challenge of net sedimentation and accumulation in estuarine navigational channels in reach of the ETM by investigating rarely available information on the bed exchange properties of sediments from the Weser estuary in field and in laboratory studies. It is the aim to provide estuary specific parameters to advance the simulation of sediment transport processes in large scale 3D morphodynamic-numerical models by improved bed exchange formulations and parametrization. This contribution focusses on results from measurements conducted in the field and in laboratory experiments, mainly related to erosion processes. By performing field trips in the ETM, cores of freshly deposited sediments have been sampled from two sites (Blexer Bogen and Nordenham) along the center of the fairway of the Weser estuary. Sediment characteristics (grain size distribution, water content, loss on ignition, density profiles) have been derived and erodibility of deposits is investigated using an erosion microcosm system quasi in situ and in the lab. Microcosm experiments are run in a closed system so sediment concentration above the lutocline increases during the experiment. This is a unique feature of this study and it is expected to produce more natural characteristics of net erosion. By reproducing natural conditions (natural sediment and deposition profiles) at first to proof comparability of results, sensitivity of determined critical shear stresses and erosion rates to parameters like density and settling times is investigated in the lab. Concentration evolution and erosion rates are the main result for an erodibility experiment from which we derive erosion parameters like the floc erosion rate, critical shear for floc erosion and critical shear for mass erosion.